Differentially expressed alternatively spliced genes in skeletal muscle from cancer patients with cachexia. Issue 1 (6th October 2017) - Narasimhan, Ashok; Greiner, Russell; Bathe, Oliver F.; Baracos, Vickie; Damaraju, Sambasivarao
Abstract: Background: Alternative splicing (AS) is a post‐transcriptional gene regulatory mechanism that contributes to proteome diversity. Aberrant splicing mechanisms contribute to various cancers and muscle‐related conditions such as Duchenne muscular dystrophy. However, dysregulation of AS in cancer cachexia (CC) remains unexplored. Our objectives were (i) to profile alternatively spliced genes (ASGs) on a genome‐wide scale and (ii) to identify differentially expressed alternatively spliced genes (DASGs) associated with CC. Methods: Rectus abdominis muscle biopsies obtained from cancer patients were stratified into cachectic cases ( n = 21, classified based on International consensus diagnostic framework for CC) and non‐cachectic controls ( n = 19, weight stable cancer patients). Human transcriptome array 2.0 was used for profiling ASGs using the total RNA isolated from muscle biopsies. Representative DASG signatures were validated using semi‐quantitative RT–PCR. Results: We identified 8960 ASGs, of which 922 DASGs (772 up‐regulated and 150 down‐regulated) were identified at ≥1.4 fold‐change and P < 0.05. Representative DASGs validated by semi‐quantitative RT–PCR confirmed the primary findings from the human transcriptome arrays. Identified DASGs were associated with myogenesis, adipogenesis, protein ubiquitination, and inflammation. Up to 10% of the DASGs exhibited cassette exon (exon included or skipped) as a predominant form of AS event. We also observed other forms of AS events such as intron retention, alternate promoters. Conclusions: Overall, we have, for the first time, conducted global profiling of muscle tissue to identify DASGs associated with CC. The mechanistic roles of the identified DASGs in CC pathophysiology using model systems is warranted, as well as replication of findings in independent cohorts.